Combined use of ionic liquid and β‐CD for enantioseparation of 12 pharmaceuticals using CE. Issue 3 (10th January 2013) - Zuo, Lihua; Meng, Heng; Wu, Jingjing; Jiang, Zhen; Xu, Shuying; Guo, Xingjie
<x xml:space="preserve">Abstract</x> In this study, the enantioseparation of zopiclone, repaglinide, chlorphenamine maleate, brompheniramine maleate, dioxopromethazine hydrochloride, promethazine hydrochloride, liarozole, carvedilol, homatropine hydrobromide, homatropine methylbromide, venlafaxine, and sibutramine hydrochloride has been investigated using β‐CD in combination with a chiral ionic liquid (IL), 1‐ethyl‐3‐methylimidazolium‐L‐lactate. The influence of the type of IL and its concentration, BGE pH, and chain length of the IL cations on the resolution are discussed. Finally, the proposed method was successfully applied for the chiral impurity determination of eszopiclone in pharmaceutical tablets after validation with respect to accuracy and precision, linearity range, selectivity, repeatability, LOD and LOQ. It is assessed that the chiral impurity determination in the commercial tables is fewer than 0.1%.